Analisis Fungsi Partai Politik Pada Pilkada Musi Banyuasin 2017 (Studi Terhadap Partai Politik Pengusung Pasangan Dodi Reza Dan Beni Hernedi) - Erik Darmawan; Anis Septiana (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Political parties are official organizations created by people who have interests and goals to control the government, by placing their members in the government through an election mechanism. The election process is inseparable from political parties, because political parties can channel the aspirations of the people, where the people can participate in it and have a strong influence on the election. The main function of political parties is to seek power, gain power and maintain it. In the 2017 Musi Banyuasin Local Election, the pairs of Dodi Reza and Beni Hernedi were carried out by 11 (eleven) political parties namely PDIP, Golkar, Democrat, Hanura, Nasdem, and PKB. As the party supporting the pair Dodi Reza and Beni Hernedi in the 2017 Musi Banyuasin Regional Election, political parties should fight in giving victory to the candidate pair that they carry by carrying out the functions of political parties as well as possible. Issues that will be discussed in this study include how the function of political parties in winning sub-regional elections and how the functions of political parties supporting the pair Dodi Reza and Beni Hernedi are assessed from the results of votes in the 2017 Musi Banyuasin Regional Election.This type of research is field research, while the type of research is qualitative, where the research procedure produces a description, which describes and describes matters relating to the problem of the function of political parties. The rationale that the researchers used in this study is the framework of thinking from Miriam Budiardjo to explain the function of political parties. The results of this study indicate that the function of political parties carried out by the party supporting the pair Dodi Reza and Beni Hernedi has not run optimally, this is evident from the high level of abstentions in the Musi Banyuasin elections in 2017.